2019
DOI: 10.1371/journal.pone.0214815
|View full text |Cite
|
Sign up to set email alerts
|

Radial profile detection of multiple spherical particles in contact with interacting surfaces

Abstract: Adhesive interactions of soft materials play an important role in nature and technology. Interaction energies can be quantified by determining contact areas of deformable microparticles with the help of reflection interference contrast microscopy (RICM). For high throughput screening of adhesive interactions, a method to automatically evaluate large amounts of interacting microparticles was developed. An image is taken which contains circular interference patterns with visual characteristics that depend on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…Obtained images of radial profiles resulting from the respective adhering or non-adhering SCPs were analyzed by a home-built software based on pattern matching. 32 Contact areas, particle radii as well as adhesion energies were calculated by the software.…”
Section: Methodsmentioning
confidence: 99%
“…Obtained images of radial profiles resulting from the respective adhering or non-adhering SCPs were analyzed by a home-built software based on pattern matching. 32 Contact areas, particle radii as well as adhesion energies were calculated by the software.…”
Section: Methodsmentioning
confidence: 99%
“…Images with RICM patterns were read out using self‐written image analysis software, and contact areas and particle profiles were evaluated using home written software. [ 57 ] After adding the SCPs to the ConA‐coated glass slides, the temperature‐dependent adhesion measurements were conducted in three cycles: 1) at 20 °C after 30 min equilibration, 2) at 45 °C after 60 min equilibration, and 3) 20 °C after 60 min equilibration.…”
Section: Methodsmentioning
confidence: 99%
“…Our adhesion studies with soft hydrogel‐based probes have shown that material parameters such as the scaffold rigidity have a strong effect on carbohydrate interactions. The SCPs are ideal for fast, high throughput optical readout but can also serve as a biomimetic colloidal probe in AFM to directly study adhesive properties on cells . This will be particularly useful to investigate the molecular mechanisms underlying the cell‐instructive properties of specifically interacting carbohydrate functionalized scaffolds …”
Section: Switchable Carbohydrate Presenting Scaffoldsmentioning
confidence: 99%
“…The adhesion leads to mechanical deformation of the probe, which can be quantified by measuring its contact radius a and overall shape by RICM. [18][19][20] With the previously determined elastic modulus of the probes, the adhesion energies can be then quantified by the JKR (Johnson-Kendall-Roberts) approach. [14] showed an identical ranking in terms of ConA binding energy.…”
Section: Effect Of Ligand Presentation On the Affinity Of Carbohydratmentioning
confidence: 99%
See 1 more Smart Citation